2014
DOI: 10.1590/0004-2730000002865
|View full text |Cite
|
Sign up to set email alerts
|

Acurácia da gordura corporal e do perímetro da cintura para predizer alterações metabólicas de risco cardiovascular em adolescentes

Abstract: RESUMOObjetivo: Avaliar a acurácia do percentual de gordura corporal (%GC) e do perímetro da cintura (PC) na predição de alterações metabólicas em adolescentes. Sujeitos e métodos: Estudo transversal com amostra probabilística de 573 estudantes de 12 a 19 anos da rede estadual de ensino de Niterói, RJ. Utilizou-se a Receiver Operating Characteristic Curve para avaliar a acurá-cia do %GC e PC na predição de alterações de pressão arterial, perfil lipídico e glicemia. Resultados: Os melhores pontos de corte do %G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…However, regardless of the criterion used to classify BMI, sensitivity was low. Moraes et al 15 tested the BMI cut-off points proposed by IOTF 19 , CDC 21 , and Conde and Monteiro 22 to predict high BP in 817 young people aged 6 to 13 years. As in the present study, sensitivity showed low values (31 to 44%), no matter the criterion used, with the Brazilian one being the most sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, regardless of the criterion used to classify BMI, sensitivity was low. Moraes et al 15 tested the BMI cut-off points proposed by IOTF 19 , CDC 21 , and Conde and Monteiro 22 to predict high BP in 817 young people aged 6 to 13 years. As in the present study, sensitivity showed low values (31 to 44%), no matter the criterion used, with the Brazilian one being the most sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cut-off points from high-income countries do not seem to be the most suitable to use in middle-and low-income ones 42 . Previous studies that tested cut-off points developed based on their samples showed high values for both sensitivity and specificity 15,39,42 . Thus, we can reasonably affirm that the success of screening for cardiovascular risk factors in children and adolescents using anthropometric indices might be related to the development and use of specific cut-off points for each population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When linked to indexes or predictive equations, these body measurements, also referred to as anthropometric indicators, can provide information on the quantity of the individual's fat mass 17,18 . Several studies have been carried out with the objective of investigating the accuracy of anthropometric measurements in the description of body fat quantity in different populations, justified by the need to gather measurements in a shorter timeframe, with lower cost and greater simplicity [19][20][21][22] . Therefore, this review proposes a response to the following central question: Can anthropometry accurately measure the body fat of PLWHA?…”
Section: Introductionmentioning
confidence: 99%